Interval data fusion with preference aggregation in wireless sensor network: energy-accuracy trade-off in presence of outliers; Journal of Physics: Conference Series; Vol. 1065 : International Measurement Confederation (IMEKO 2018) - Khudonogova L. I. Ludmila Igorevna (2018, 2018)
Title screen